Perkembangan Seni Beladiri Benjang Gulat di Kecamatan Ujungberung (1920 - 2021) - Husna Aulia Jannah; Ading Kusdiana (Priangan: Journal of Islamic Sundanese Culture, 2023)
AbstractArt is one of the seven cultural elements proposed by Koentjaraningrat. The growth of the arts is also inseparable from the characteristics or peculiarities of a particular society. The same goes for the martial art of Benjang Wrestling. This article discusses the development of Benjang Wrestling martial arts in Ujungberung district. The writing of this article aims to explain how the beginning of the emergence of Benjang art and the development of Benjang Wrestling martial arts. The research method used in writing this article is a historical method that has four stages, namely heuristics, criticism, interpretation, and historiography. The results of research from the sources that have been studied show that Benjang already appeared in the middle of the 19th century, but began to be known to the wider community since the beginning of the 20th century which then continued to develop and had its own techniques. Although it was banned during the New Order era, after the reform, Benjang Wrestling martial arts activists tried to maintain the existence of Benjang Wrestling, especially until now. This can be seen from the establishment of an organization that aims to organize and house the martial arts practitioners of Benjang Wrestling. Keyword: Artistry, Benjang, Traditional  AbstrakKesenian merupakan salah satu dari tujuh unsur kebudayaan yang dikemukakan oleh Koentjaraningrat. Pertumbuhan kesenian juga tidak dapat dipisahkan dari ciri atau kekhasan masyarakat tertentu. Begitu pula dengan Seni beladiri Benjang Gulat. Artikel ini membahas mengenai perkembangan seni beladiri Benjang Gulat di kecamatan Ujungberung. Penulisan artikel ini bertujuan untuk menjelaskan bagaimana awal mula munculnya kesenian Benjang serta perkembangan seni beladiri Benjang Gulat. Metode penelitian yang digunakan dalam penulisan artikel ini adalah metode sejarah yang memiliki empat tahapan, yaitu heuristik, kritik, interpretasi, dan historiografi. Hasil penelitian dari sumber yang telah diteliti menunjukkan bahwa Benjang sudah muncul pada pertengahan abad-19, tetapi mulai dikenal masyarakat luas sejak awal abad ke-20 yang kemudian terus  berkembang dan memiliki teknik-teknik tersendiri. Meskipun sempat dilarang pada era Orde Baru, pasca reformasi pegiat seni beladiri Benjang Gulat berusaha untuk mempertahankan eksistensi Benjang Gulat khususnya hingga saat ini. Hal ini dapat dilihat dari didirikannya organisasi yang bertujuan untuk mengatur dan menaungi para pelaku seni beladiri Benjang Gulat. Kata kunci: Kesenian, Benjang, Tradisional